Purchase Intentions as moderating variables in relationship between Halal Awareness Toward Buying Behavior - Noor Efa; Muhammad Husni Mubarok (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
This study aims to analyze buying behavior for Uliq food products by considering the halal certification, halal credence, and halal awareness through a mediating role of purchase intention. The study employed a survey method and data were collected from 101 respondents. Structural equation modeling was employed as a data analysis tool. The results show that the halal certification and halal credence have not a significant effect on the purchase intention. However, halal awareness has a significant impact on purchase intention. Then, purchase intentions has a significant effect on the buying behaviour.